Affective stimuli in behavioural interventions soliciting for health check-up services and the service users' socioeconomic statuses: a study at Japanese pachinko parlours. Issue 5 (12th January 2018) - Kondo, Naoki; Ishikawa, Yoshiki
Abstract : Background: Socioeconomically vulnerable people are likely to have more health risks because of inadequate behaviour choices related to chronic social stresses. Brain science suggests that stress causes cognitively biased automatic decision making, preferring instant stress relief and pleasure (eg, smoking, alcohol use and drug abuse) as opposed to reflectively seeking health-maintenance services (eg, health check-ups). As such, hedonic stimuli that nudge people towards preventive actions could reduce health behaviour disparities. The purpose of this intervention study was to test this hypothesis. Methods: An instant health check-up service company had 320 health check-up sessions at pachinko (Japanese gambling) parlours; 1721 persons in intervention sessions and 6507 persons in control sessions received the service. The stimuli the company used in the intervention sessions were young women wearing mildly erotic nurse costumes, who solicited the pachinko players for health check-up services. We compared the prevalence of socioeconomically vulnerable individuals between the intervention and control sessions, adjusting for individual-level and parlour-level potential confounders. Results: Even adjusting for health risks and within-parlour clustering, the intervention sessions gathered more socioeconomically vulnerable customers than the regular sessions. Compared with control sessions, in intervention sessions the adjusted prevalence ratios were 1.15 (95% CI 0.99 to 1.35) for not having a job (vs having a job) and 1.36 (95% CI 1.00 to 1.86) for holders of National Health Insurance (which includes more socially vulnerable people than other insurance programmes). Conclusion: The results supported our hypothesis. Offering health check-up opportunities equipped with 'tricks' that nudge people to act might be effective for anyone but is potentially more valuable for socially vulnerable people. Ethical discussions are needed to further consider the use of erotic stimuli and other essential drivers of human behaviour.